Pengaruh Penerapan Kurikulum Merdeka Terhadap Hasil Belajar Matematika Siswa SMP Negeri 4 Buton - Isra Miranda; Rasmuin Rasmuin; Herlawan Herlawan (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2026)
The problem statement in this study is, is there any significant Effect of the Implementation of the Independent Curriculum on the Mathematics Learning Outcomes of students at SMP Negeri 4 Buton? The purpose of this study was to determine the Effect of the Implementation of the Independent curriculum on the mathematics learning outcomes of Grade SMP Negeri 4 Buton. This study used an ex post facto research method. The population was all grade VIII students in the even semester of SMP Negeri 4 Buton, consisting of three classes. The sample size was 44 students, using cluster random sampling. The instruments used a questionnaire and essay- based diagnostic test. The research results revealed that the independent curriculumon student learning outcomes, specifically an essay test, based on calculations using Simple Linear Regression using the R_L2DIKTI_22 Series A application. A p-value of 0.000 was obtained for a significance level of 0.05 (5%). Therefore, a significance value 0.000 < 0.05 indicates that the HI is accepted. Therefore, it can be concluded that the implementation of the independent curriculum has a significant effect on the mathematics learning outcomes of eight-grade students at SMP Negeri 4 Buton.